Transmissible antimicrobial resistance in Escherichia coli isolated from household drinking water in Ibadan, Nigeria. - Akeem G Rabiu; Olutayo I Falodun; Rotimi A Dada; Ayorinde O Afolayan; Olabisi C Akinlabi; Elizabeth T Akande; Iruka N Okeke (PLoS ONE)
Contaminated household water in peri-urban communities is a reservoir for virulent Escherichia coli, but its role in the environmental transmission of antibiotic resistance genes (ARGs) remains poorly understood. This study characterized E. coli from household water and additionally aimed to investigate the transmissibility of ARGs from drug-resistant isolates. Twenty-five E. coli isolates from thirteen household well water sources were tested for resistance to 14 antibiotics by disc diffusion and whole-genome sequenced using the Illumina platform. The ARGs and plasmid replicon types were respectively predicted using ResFinder and PlasmidFinder. Multidrug-resistant strains carrying plasmid replicons found in unrelated strains were conjugated with nalidixic acid-resistant (NALR) E. coli C600 using the solid plate method. Fifteen isolates displayed a multi-drug resistance (MDR) phenotype, with 18 possessing ARGs that confer resistance to trimethoprim-sulfamethoxazole, macrolide, sulphonamide, aminoglycoside, chloramphenicol, β-lactams, and tetracycline. Fifteen of the 25 isolates belonged to sequence type detected more than once, and fourteen of these were multidrug resistant. Through solid plate mating, beta-lactam-resistant qnrS1-tet-dfrA14-positive strains bearing IncFI-, IncHI2, and IncHI2A successfully transferred ampicillin resistance to a nalidixic acid-resistant derivative of E. coli-C600. This research highlights the urgent need to safeguard household water sources against fecal contamination to curb the dissemination of ARGs among bacterial populations in this environment.